Physical Extraction Of Flagella Via Ultrasonication From Bacillus Subtilis 168 With Various Control Elements - Leong, Kah Yan (Universiti Sains Malaysia, 2020)
Flagella was commonly known as the tail of bacteria. The major structural protein of bacterial flagella is called flagellin. Flagella have a potential to become biodegradable nanotube and important for drug delivery, electronic or semiconductor. There are still lack of research about flagella separation and purification. In this research, the morphology of the flagella and basal body for Bacillus subtilis 168 was investigated by scanning electron microscope and transmission electron microscope. The characterization of flagella was found that difference between flagella and cell body is nitrogen (N), magnesium (Mg) and Sulphur (S) by energy-dispersive X-ray spectroscopy.